Jia-Wei-Kai-Xin-San, an Herbal Medicine Formula, Ameliorates Cognitive Deficits via Modulating Metabolism of Beta Amyloid Protein and Neurotrophic Factors in Hippocampus of Aβ1-42 Induced Cognitive Deficit Mice - Zhu, Yue; Shi, Yiwei; Cao, Cheng; Han, Zhenxiang; Liu, Mengqiu; Qi, Mingzhu; Huang, Renjie; Zhu, Ziqiang; Qian, Dawei; Duan, Jin-ao (Frontiers in Pharmacology, 2019)
Jia-Wei-Kai-Xin-San (JWKXS) is a Chinese medicine formula applied for treating morbid forgetfulness in ancient China. Today, this formula is frequently applied for Alzheimer’s disease and vascular dementia (VD) in clinic. Here, we developed it as granules and aimed to evaluate its anti-AD effect on β amyloid protein 1–42 (Aβ1-42) induced cognitive deficit mice and reveal the possible molecular mechanisms. Firstly, daily intra-gastric administration of chemically standardized of JWKXS granules for 7 days significantly ameliorated the cognitive deficit symptoms and inhibited cell apoptosis in hippocampus on Aβ1-42 injection mice. JWKXS granules significantly decreased Aβ level, increased superoxide dismutase activity and decreased malondialdehyde level in hippocampus of model mice. It also restored acetylcholine amounts, inhibited acetylcholinesterase activities and increased choline acetyltransferase activities. In addition, JWKXS granules enabled the transformation of precursors of NGF and BDNF into mature forms. Furthermore, JWKXS granules could regulate gene expressions related to Aβ production, transportation, degradation and neurotrophic factor transformation, which led to down-regulation of Aβ and up-regulation of NGF and BDNF. These findings suggested that JWKXS granules ameliorated cognitive deficit via decreasing Aβ levels, protecting neuron from oxidation damages and nourishing neuron, which could serve as alternative medicine for patients suffering from AD.